2007
DOI: 10.1038/cr.2007.78
|View full text |Cite
|
Sign up to set email alerts
|

Physiological functions of Atg6/Beclin 1: a unique autophagy-related protein

Abstract: Abbreviations: activating molecule in Beclin 1-regulated autophagy (Ambra1); autophagy-related (Atg); Bcl-2-homology-3 (BH3); coiled-coil domain (CCD); cytoplasm to vacuole targeting (Cvt); evolutionarily conserved domain (ECD); embryoid bodies (EB); endoplasmic reticulum (ER); hypersensitive response (HR); herpes simplex virus type 1 (HSV-1); Niemann-Pick C (NPC); programmed cell death (PCD); phosphatidylethanolamine (PE); phosphatidylinositol (PtdIns); UV irradiation resistance-associated gene (UVRAG); vacuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
394
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(414 citation statements)
references
References 86 publications
13
394
1
6
Order By: Relevance
“…Effect of combined ectopic Beclin-1 expression and rapamycin treatment on autophagy induction and cell growth Increased Beclin-1 expression regulates autophagy tightly by initiating autophagosome formation (Cao and Klionsky, 2007). Ectopic expression of Beclin-1 failed to modulate apoptosis (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Effect of combined ectopic Beclin-1 expression and rapamycin treatment on autophagy induction and cell growth Increased Beclin-1 expression regulates autophagy tightly by initiating autophagosome formation (Cao and Klionsky, 2007). Ectopic expression of Beclin-1 failed to modulate apoptosis (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Beclin-1 is the first identified autophagy-related gene that could reflect the level of autophagy (Cao and Klionsky, 2007;Zeng et al, 2006). It plays a crucial role in the process of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Beclin-1, the mammalian orthologue of the yeast Apg6/ Vps30 gene, is considered as the first identified autophagy gene product (Zeng et al, 2006;Cao and Klionsky, 2007). It is involved in nucleation and locus on chromosome 17q21, which is isolated as a Bcl-2-interacting protein (Miracco et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Despite autophagy being a primarily cytoprotective mechanism, excessive self-digestion can also be detrimental (Cao and Klionsky 2007;Pattingre et al 2008). The most significant genes to have been studied to date are BECLIN1 and LC3B (Chen and Karantza-Wadsworth 2009;Miracco et al 2010), with many studies having demonstrated the influence of deregulation in their expression during tumorigenesis (Levine 2007;Roy and Debnath 2010).…”
Section: Introductionmentioning
confidence: 99%